Success rate of nasogastric tube insertion in anesthetized, intubated, adult patients: A comparison between endotracheal tube cuff inflated and deflated states - Nazimuddin Paik; Chakraborty, Soma; Mandal, Sangita; Sarfraaz Rahman; Sayantan Modak; Chakraborty, Arpan; Mandal, Mohanchandra (Asian Journal of Medical Sciences, 2024)
Background: Although proper placement of nasogastric tube (NGT) is a simple procedure, it can turn into a tedious task in an anesthetized intubated patient due to the absence of propulsive movement of swallowing. Different techniques of NGT placement are in vogue in clinical practice with varying success rates. The effect of endotracheal tube (ETT) cuff deflation on the success rate of NGT placement has been evaluated only in one study, and the first-attempt success rate was reported to be not high (55%). Aims and Objectives: This interventional study primarily aimed at comparing the success rates of proper placement of NGT in the first attempt between the ETT cuff inflated and deflated states. Materials and Methods: The present study was carried out on 244 adults scheduled for abdominal surgeries requiring NGT insertion. Patients received NGT placement with either an ETT cuff inflated (Group A, n=122) or ETT cuff deflated (Group B, n=122). The success rate of correct placement of NGT in the first attempt was the primary outcome. Procedure time and adverse events were also evaluated. Results: Considerably higher success rate of correct placement of NGT in the first attempt was noted with ETT cuff deflated over-inflated state (85.2% vs. 55.7%, P<0.001). A shorter procedure time was observed with ETT cuff deflated over an inflated state (16.8±7.0 vs. 38.1±27.33 P<0.001). Adverse events were comparable. Conclusion: The higher success rate of correct NGT placement was observed with endotracheal cuff deflated state over cuff-inflated state. Faster placement of NGT was noted with endotracheal cuff deflated state.